THE ENFORCEMENT OF GOMPONG IN THE QANUN OF ACEH AND ITS RELATIVE POSITION IN THE INDONESIAN CONSTITUTION - Iskandar, Mizaj (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
This paper aims to learn how the Qanun of Aceh, particularly Qanun No. 4 on Mukim and Qanun No. 5 on Gampong Government enforce Gampong as a government body. It further compares the hierarchical relationship between the qanun and the higher regulations in Indonesia such as Village Government Act No. 32 of 2004, Privileges of Aceh Act No. 44 of 1999, Special Autonomy No. 18 of 2001 and Aceh Government Act No. 11 of 2006. The study found that the Qanun integrates Acehnese identity coupled with the Islamic values into the Gampong institution. The Qanun on Gampong Government, in fact, does not negate any higher regulations in the Indonesian constitution. The principle of decentralization implemented post-Orde Baru requires a massive change in the government system in Indonesia from the centralized system of local state government, to local self-government and finally the decentralized system of the local community. The Qanun on Gampong government is in line with the local community spirit due to greater public participation channeled through Reusam Gampong. Reusam Gampong is the public aspiration, and its application shall not conflict with the higher regulation. In its cultural manifest, Resuam Gampong is an instrument that promotes the marriage between culture and religion into a single government body.